Photon upconversion for the enhancement of microfluidic photochemical synthesis. Issue 45 (21st August 2019) - Wu, M.; Moser, B. A.; Steeves, T. M.; Figueroa, A.; Wallace, B. M.; Kim, S. T.; Esser-Kahn, A. P.; Steinhardt, R. C.
Abstract : Photochemical transformations are greatly improved in yield by fluidic reactor technology. Abstract : Photochemical transformations are greatly improved in yield by fluidic reactor technology. However, the delivery of synthetically-active light to the reactants is a challenge. Here, we use upconversion in a bio-inspired microreactor to augment the flux of critical wavelengths of light. This new technology increased of a model reaction by converting a greater portion of sunlight to photochemically-available photons.